The effect of flexing influencer and customer attitude on social media on cryptocurrency investment decisions (study on gen z in north Jakarta) - Sephiani, Regina; Astuti, Widi (Enrichment : Journal of Management, 2025)
This study is driven by the growing impact of flexing influencer content on social media toward Generation Z perspectives and investment decisions, especially in the high-risk cryptocurrency sector. The research examines whether flexing influencers and customer attitudes, either individually or jointly, affect cryptocurrency investment decisions. Using a quantitative explanatory approach, data were collected from 385 Generation Z respondents in North Jakarta through simple random sampling and analyzed with PLS-SEM. Findings show that both variables significantly influence investment decisions, partially and simultaneously. However, with an R-Square value of 0.124, they explain only 12.4% of the variance, indicating the presence of other dominant factors beyond this model.